Deficiências e incapacidades em vítimas de acidentes de trânsito atendidas em unidades de urgência e emergência em Mato Grosso - Duarte, Flávia Guimarães Dias (2016)
Traffic accidents are considered a serious public health problem. In Brazil, they are among the leading causes of morbidity and mortality with more than 45,000 deaths and approximately 170,000 hospitalizations in 2013. However, little is known about the consequences of injury. The aim of the study was to analyze disabilities in non-fatal victims of traffic accidents in urgent and emergency units. Therefore, we conducted a cross-sectional study using the International Classification of Functioning, Disability and Health (ICF) which enables to identify the functionality and the living conditions of a given population. ICF allows to describe situations related to the individual functions and its restrictions and serves as a framework to organize this information from domains: body functions, body structures, activities and participation and environmental factors. We studied 228 victims of traffic accidents assisted in urgent and emergency units of four municipalities in the state of Mato Grosso. Predominated young, male and motorcyclists. With regard to the deficiencies in the body functions were more impaired sensory and pain (49.3%) and neuromusculoskeletal (45.8%), while in structure, 85.5% of the failures were related to movement. Both had moderate severity. Regarding the difficulty in performing some activity or participate in social life, related to mobility (42.0%) were the most affected, with moderate severity (30.5%). Among the environmental factors, services, systems and policies they represented the greatest barrier to the victims (66.3%) and among the risk factors prevailed support and relationships with family and friends (40.9%). In addition to describing the characteristics of non-fatal traffic accident, the study revealed the magnitude of the disabilities caused by this injury, demonstrating the possibility of using the ICF as an important tool for knowledge about the health and quality of life this population.